Plasma ?-carotene concentrations in pregnancies, newborn infants and their mothers - Ziyakarakilcik, A.; Aksakal, Mosul; Baydas, G.; Sozcri, R.; Ayata, A.; Simsck, M. (My University, 1996)
Concentrations of ?-carotene were determined in maternal and fetal blood. The samples were collected from 33 mothers, their 33 newborns and 50 pregnant and 29 non-pregnant women, ?-carotene concentrations of the non-pregnant, pregnant, newborn infant and their mothers were 140.31,171.54,63.57and 175.74 ?g/dl, respectively. There was a significant correlation (P<0.001) between ?-carotene values of the maternal plasma and cord plasma. Mean matemal plasma ?-carotene concentration was higher (P<0.0005) than that of the cord. These results suggest that plasma transport capacity of ?-carotene was low from mother to their fetus (JPMA 46:77,1996).
Keywords: Adult; beta Carotene; Female; Fetal Blood; Humans; Infant, Newborn; Male; Pregnancy; Reference Values; beta carotene; adult; article; blood; chemistry; female; fetus blood; human; male; newborn; pregnancy; reference value